The effects of participative decision making on the relationship between leadership style and organizational commitment - Lim, Sze Chia, 1986; Ishak Mad Shah, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2010)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2010